4
$\begingroup$

I am new to statistics and I happen to came across this property of MGF:

Let $X$ and $Y$ be independent random variables. Let $Z$ be equal to $X$, with probability $p$, and equal to $Y$, with probability $1 − p$. Then, $$M_Z(s)= p M_X(s) + (1 − p) M_Y(s).$$

The proof is given that

$$M_Z(s)= E[e^{s Z}]= p E[e^{s X}] + (1 − p)E[e^{s Y}]= p M_X (s) + (1 − p)M_Y (s)$$

But I do not understand, can someone show me a full proof as in showing the conditioning on the random choice between X and Y, as in why the following holds

$$M_Z(s)= E[e^{s Z}]= p E[e^{s X}] + (1 − p)E[e^{s Y}]$$

Thanks very much.

| cite | improve this question | | | | |
$\endgroup$
  • $\begingroup$ Apply the law of total probability to get the distribution of $Z$. Then compute the expectation. $\endgroup$ – Dilip Sarwate Mar 29 '13 at 13:24
  • $\begingroup$ Is it possible to show some working? I don't see how the law of total probability and expectation works here. Sorry, I am new in stats $\endgroup$ – user23672 Mar 29 '13 at 13:40
  • $\begingroup$ The law of total probability allows you to express the law of $Z$ as a weighted sum (weights $p$ and $(1-p)$) of the laws of $X$ and $Y$. Then, $E[e^{tZ}]$ can be calculated from the law of $Z$. I assume that you know the formula for finding $E[g(Z)]$ using the law of $Z$? The sum (or integral) for $E[e^{tZ}]$ can then be expressed as a weighted sum of $E[e^{tX}]$ and $E[e^{tY}]$. $\endgroup$ – Dilip Sarwate Mar 29 '13 at 13:54
  • $\begingroup$ Each of these three lines says the same thing: it is an axiom of probability that conditional probabilities multiply in this way, whence so do expectations (and, of course, MGFs, because they are expectations). $\endgroup$ – whuber Mar 29 '13 at 13:58
  • $\begingroup$ Dilip, I assume that you know the formula for finding E[g(Z)] using the law of Z? (for this, no I don't). How do u find the distribution of Z to get its expectation? $\endgroup$ – user23672 Mar 29 '13 at 14:37
3
$\begingroup$

You may also see it this way: consider another Bernoulli RV $\Theta$ which is $0$ with probability $p$ and $1$ with probability $1-p$ (so $P(\Theta = 0) = p, P(\Theta = 1) = 1-p$). This variable selects either $X$ or $Y$ with the given probability $p$ and $1-p$. Then the PMF of $Z$ is $$P(Z = k) = P(X = k, \Theta = 0) + P(Y = k, \Theta = 1)$$ $$ = P(X=k)P(\Theta = 0) + P(Y = k)P(\Theta = 1)$$ due to the independence of $\Theta$ from $X,Y$ so $$P(Z = k) = p P(X = k) + (1-p) P(Y = k)$$ The MGF is given by $$\mathbf{E}[e^{s Z}] = \sum_{k \in \chi} e^{s k} P(Z = k) = \sum_{k} p e^{s k} P(X = k) + (1-p)e^{s k} P(Y = k)$$ where $\chi$ is the set of possible values of $Z$, so $$\mathbf{E}[e^{s Z}] = p \mathbf{E}[e^{s X}] + (1-p) \mathbf{E}[e^{s Y}]$$

| cite | improve this answer | | | | |
$\endgroup$
2
$\begingroup$

Similar to the other answer, but using the conditional expectation more explicitly.

Flip a coin $\newcommand{\E}{\mathbb{E}} U\sim\mathrm{Ber}(p)$ independently of $X$ and $Y$. Let $Z=UX+(1-U)Y$. Easy to prove: $$\E\left[e^{tZ}\mid U\right]=U\,\E\left[e^{tX}\right]+(1-U)\,\E\left[e^{tY}\right] \, ,$$ almost surely. Tower property: $\E\left[e^{tZ}\right]=\E\left[\E\left[e^{tZ}\mid U\right]\right]=p\,M_X(t)+(1-p)\,M_Y(t)$. $\quad\square$

Take a look at this question if you have any doubts about $\E[e^{tZ}\mid U]$ being itself a random variable which is a function of $U$.

| cite | improve this answer | | | | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.